Efektivitas Penyelesaian Tindak Pidana Ringan Melalui Lembaga Adat (Sarak Opat) - Achmad Surya; Suhartini Suhartini (Jurnal Hukum IUS QUIA IUSTUM, 2019)
Thisstudy aims firstly to observe the effectiveness of minor criminal acts settlement through Sarak Opat in Central Aceh District. Second, it is to find out what constraints being faced by Sarak Opat are in settling the minor criminal acts in Central Aceh District. The method used in this study was empirical legal research or sociological legal research. The types and sources of data used in this study included library research and field  research.  The  data  analysis  technique  was  conducted  through  a  descriptivequalitative  method  by analysing the data obtained from the primary and secondary data sources. This was then continued with a thorough discussion and a conclusion, based on the discussion, was drawn in response to the problems studied. The results of the research showed first that it was still ineffective now that the people becoming the victims of criminal acts more believed in the police as the law enforcement officials rather than the settlement through the traditional institution of Sarak Opat. Second,the constraints faced by Sarak Opat in the settlement of minor crimes in Central Aceh Regency, included 1). The lack of understanding of the traditional institution of  Sarak  Opat;  2).  Customary  sanctions  not  giving  any  deterrent  effects  on  the  perpetrator;  3).  No documented  dispute  settlement  by  traditional  institution  Sarak  Opat;  4).  Lack  of  coordination  between traditional institution Sarak Opat and Police Department.